Effects of situated game teaching through set plays on middle school students’ soccer skills and game performance - DERVENT, FATİH (My University, 2023)
Purpose: To examine the effects of the Situated Game Teaching through Set Plays (SGTSP) curricular model on secondary school students’ soccer skills and game performance during a 10-lesson unit. Methods: A quasi-experimental design with/without a repeated measure was used to examine the effectiveness of the SGTSP model in comparison with a technique-focused approach. A convenient sample of 27 sixth graders from two classes participated in this study. Classes were randomly assigned to conditions. Data were collected from soccer skill tests and game performance coding instrument. Analysis of variance with or without a repeated measure was conducted to analyze the data. Results: Participants’ ball controlling skill significantly improved for both groups over time. Their shooting and dribbling skills did not improve for both groups over time. No statistical differences were found in participants’ changes in ball controlling, shooting, and dribbling skills over time between the two conditions. Participants in the SGTSP condition had better offensive off the ball, offensive with the ball, overall offensive decision making, and overall decision making than those in the comparison condition. Conclusions: The findings provided initial evidence supporting the effectiveness of the SGTSP model on developing students’ decision making in the game plays. Participants taught by SGTSP had similar skill performance as those taught by a technique-focused approach.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Surgery Medicine Sciences; Orthopedics and Traumatology; Social Sciences and Humanities; Sociology; Education; Health Sciences; Klinik Tıp (MED); Sosyal Bilimler (SOC); Klinik Tıp; Sosyal Bilimler Genel; REHABİLİTASYON; ORTOPEDİ; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Clinical Medicine (MED); Social Sciences (SOC); CLINICAL MEDICINE; SOCIAL SCIENCES, GENERAL; REHABILITATION; ORTHOPEDICS; EDUCATION & EDUCATIONAL RESEARCH; Ortopedi ve Spor Hekimliği; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Sosyal Bilimler ve Beşeri Bilimler; Orthopedics and Sports Medicine; Physical Therapy, Sports Therapy and Rehabilitation; Social Sciences & Humanities; curriculum model; game scenarios; relational analysis; situated learning